The Effect of Light Distance on Aeroponic Potato Seed Production in The Tropical High Land - Eni Sumarni; Loekas Soesanto; Whidiatmoko Herry Purnomo; Priswanto Priswanto (The University of Lampung, 2022)
Aeroponic potato seed production in the highlands during foggy weather is an obstacle in increasing the number of tubers. Research that has been done previously is the addition of artificial light to support the growth and yield of potato seeds in the highlands. Nevertheless, from these results, there were still some plants that did not have optimal growth. It was suspected that the lamp height affects the growth and yield of aeroponic potato plants. The purpose of this study was to determine the effect of lamp distance on artificial lighting on the growth and yield of aeroponic potatoes. The factors that were tried were the height of the lamp from the aeroponic box 110 cm, 120 cm, and 130 cm. The lamps used: 18 Watt red blue LED (RB) and 10 Watt white fluorescent lamp. The design used was a completely randomized design. Growth observation data and results were analyzed by F test followed by Duncan's Multiple Distance Test (DMRT) 5%. The results showed that the combination of RB LED lamps with a height of 110 cm produced the highest number of bulbs of 31,7 per plant. The weight of aeroponic potato tubers in the highlands with the highest yield was obtained from a combination of 110 cm (29,3 g) RB LED lights. Keywords: Aartificial lighting, hydroponics, granola, greenhouse, tropical Indonesia